2020
DOI: 10.1002/cam4.3150
|View full text |Cite
|
Sign up to set email alerts
|

Circulating activated lymphocyte subsets as potential blood biomarkers of cancer progression

Abstract: The objective of this study was to predict the value of lymphocyte subsets in cancer progression. Peripheral blood was obtained from 327 untreated patients with cancer and 158 healthy volunteers. Levels of lymphocyte subsets were determined by flow cytometry. There were decreased levels of natural killer (NK) cells, CD8 + T cells, and naïve CD4 + /CD4 + T cells in untreated patients with cancer compared to those in healthy controls. Inversely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…The research suggested that ACL could be served as a potential peripheral blood immune impairment markers in patients with BC to monitor the immune function, and predict the prognosis and therapeutic effect. It is the rst time to report the clinic value of peripheral ACL in BC, though some research suggested that total number of peripheral blood lymphocytes was associated to the prognosis and therapeutic effect [13,14,15,29,30]. Firstly, just as our study showed, there was no signi cant difference in the percentages of CD3 + , CD3 + CD4 + , CD3 + CD8 + , B, and NK cells between NCs and BC patients.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The research suggested that ACL could be served as a potential peripheral blood immune impairment markers in patients with BC to monitor the immune function, and predict the prognosis and therapeutic effect. It is the rst time to report the clinic value of peripheral ACL in BC, though some research suggested that total number of peripheral blood lymphocytes was associated to the prognosis and therapeutic effect [13,14,15,29,30]. Firstly, just as our study showed, there was no signi cant difference in the percentages of CD3 + , CD3 + CD4 + , CD3 + CD8 + , B, and NK cells between NCs and BC patients.…”
Section: Discussionmentioning
confidence: 52%
“…Traditionally, the ACL was measured by dual-platform technology by which the percentages of lymphocyte subsets measured by ow cytometry was combined with the absolute lymphocyte count measured by an automatic hematology analyzer,which produced obvious errors among different laboratories [11][12][13][14]. Here, we adopted the single-platform technology to carry out the detection entirely on the ow cytometer, which signi cantly improved the accuracy of the analysis.…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…Numerous studies have indicated the prognostic value of peripheral blood lymphocyte subsets in cancer patients (36)(37)(38). However, the prognostic roles of peripheral blood lymphocyte subsets in NSCLC patients treated with ICIs is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes play a crucial role in cancer development, either in anti-tumor immunity or pro-tumor immunity (18). Circulating lymphocyte subsets have been observed to be associated with the prognosis of several types of cancer (19)(20)(21), and to be affected by various treatments including chemotherapy (17,22). Some research has shown that compared to T cells, the number and function of B cells are more adversely affected by chemotherapy (23), and the alternations of immune function may last for a longer period than the treatment (17).…”
Section: Introductionmentioning
confidence: 99%